Standardization of Shatpala Ghrita w.s.r Pharamaceutico-Analytical and Antioxidant Study - Verma, Vijay Shankar; Kumar, Sanjay; Meena, Jitendra; Shyama (International Research Journal of Ayurveda & Yoga, 2022)
Sneha kalpana is one of the unique and commonly prescribed Ayurvedic dosage form in day to day practice having increase potency, palatability, shelf life etc. Although lots of verities of Snehas are described in Ayurvedic texts, the most common amongst them are Taila & Ghrita kalpana. It is a pharmaceutical process to prepare oleaginous medicament from the substances like Kalka, Sneha Dravya and Drava Dravya in specific proportion by subjecting to unique heating pattern and duration, to fulfil certain parameters according to need of therapeutics (i.e. Mridu, Maddhya & Khar). Sneha Siddha (fat soluble) drugs have better pharmacokinetic action in comparison to other dosage forms, because the use of Ghrita as a base is presumably to extract or hold lipid soluble active ingredients from the herbal drugs used and these lipid soluble substances readily permeate into the bio membrane of cells due to its lipid nature. The conceptual study suggests that Shatapala Ghrita is used to treat Jwara mainly Vata and Kapha Dosha predominant. Standardization is the process of developing and agreeing upon technical standards and provides numerical value which quantifies the parameter and thus denotes the quality of formulations. Murchana performed on Go-Ghrita makes it a better medium for the solubility of the drug and imparts all the specific properties to the Ghrita which can be used to increase the efficacy of the drugs. Hence, it can be inferred that the medicated Ghrita should be prepared by taking the Murchhita Ghrita as ingredient rather without Ghrita Murchhana. In so many Ghrita kalpanas, Shatapala Ghrita is a ghee based Ayurvedic formulation described in Samhitas and various Rasa texts with different name and slightly changes in contents. It has broad indication such as enlarge spleen (splenomegaly), Vishamajwara, Mandaagni, Rajyakshma etc.